Efficacy of Probiotics in Preventing Antibiotic-Associated Diarrhea in Outpatients - Alghamdi, Raid Hassan D; Alghamdi, Mohammed Dhaifallah Mohammed; Alghamdi, Amro Ali Safar; Waznah, Abdullah Saleh Mohammed; Shammaa, Sultan Ismail; Alomari, Adel Ali Masoud; Alotaibi, Ziyad Safar Safar; Albeladi, Ahmed Hamed; Alharbi, Khaled Naffa; Almalki, Salman Mohammed Hassan; Alzahrani, Abdulrahman Abdulaziz Ibrahim; Alotaibi, Mohammed Flaih Frees; et al. (Journal of Posthumanism, 2024)
Antibiotic-associated diarrhea (AAD) is a prevalent adverse influence of antibiotic management, particularly among outpatients receiving broad-spectrum or prolonged antibiotic courses. AAD can negatively impact treatment adherence, quality of life, and healthcare costs, and in some cases may progress to severe complications such as Clostridioides difficile infection. Probiotics were suggested as a preventive strategy to restore gut microbiota balance and decrease the frequency of AAD. However, variability in probiotic strains, dosages, and management regimens has led to inconsistent findings across studies, necessitating a comprehensive assessment of their efficiency and safety in outpatient settings. Methods: A systematic review has been performed utilizing EMBASE, Library, MEDLINE, Scopus, Cochrane and Web of Science. Searches employed keywords and MeSH terms including “antibiotic-associated diarrhea,” “AAD,” “probiotics,” “outpatients,” “Lactobacillus,” “Bifidobacterium,” and “Saccharomyces boulardii.” Eligible investigations involved randomized controlled trials (RCTs) and cohort investigations involving adult or pediatric outpatients receiving antibiotics with concurrent probiotic supplementation. Extracted data encompassed study design, probiotic strains and doses, incidence of AAD, duration and degree of diarrhea, and reported adverse events. Results: Five studies met the inclusion criteria. Probiotic supplementation was related to a significant decrease in the frequency of AAD in comparison with placebo or no intervention, with relative risk reductions ranging from 30% to 60%. Multistrain probiotics and Sacchar.